Acquiescence and Resistance in Disconfirming Responses to Polar Questions. Issue 2 (17th February 2017) - Lee, Seung-Hee
Abstract : Here I examine three forms of disconfirming responses to polar questions in Korean conversation: type-conforming "no" responses, direct nonconforming responses such as repetitions of the question with negation, and nondirect nonconforming responses such as replacements. The use of these forms tends to be different depending on the particular form of question. When questions are in unmarked form with no interrogative endings, indexing a knowing stance, type-conforming responses accept the question and the questioner's epistemic stance. Both direct and nondirect nonconforming responses, by contrast, resist the question's constraints and the knowing stance taken by the questioner. When questions are marked with interrogative endings, encoding an unknowing stance, "no" responses resist the questioner's epistemic stance, treating the matter at hand as already known. Direct nonconforming responses depart from the terms and constraints of the question, whereas nondirect nonconforming responses provide new information addressed to the question's agenda, accepting the questioner's unknowing stance.